The effect of aromatherapy with Rosa damascena essential oil on sleep quality in children - A.S. Keyhanmehr; M. Movahhed; S. Sahranavard; L. Gachkar; M. Hamdieh; Sh. Afsharpaiman*; H. Nikfarjad (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Sleep disorder is one of the main problems in children. Poor sleep quality can lead to adverse effects on their growth and development. Aromatherapy is a kind of method for improving sleep. In Iranian traditional medicine, inhaling Rosa damascena has been recommended for treating sleep disorder. Due to the side effects of chemical drugs and trend to alternative medicine due to less complication, the aim of this study was to investigate the effect of aromatherapy with Rosa damascena essential oil on sleep quality in children. Methods: This study was an experimental before and after study that conducted in 30 children with sleep disorder. Children inhaled 5 drops of Rosa damascena essential oil on a cotton ball before sleep for 20 min (2 weeks). Before and after intervention, BEARS questionnaire was asked. Wilcoxon signed-rank test was used for comparisons by SPSS software. Results: The results of this study showed that resistance to sleep, difficulty waking in the morning, nightmare and waking up during the night in children decreased (p